Peningkatan Kapasitas Lansia Menghadapi Bencana Gempa Di Gedung Dengan Metode Bernyanyi Di Posyandu Lansia GBI Setia Bakti Kediri - Heru Suwardianto; Vitaria Wahyu Astuti (Pelita Abdi Masyarakat, 2021)
Background : Earthquake disasters in buildings can occur anytime, anywhere and in any situation. Aggregates of the elderly are a vulnerable group with a greater possibility of victims. Capacity building is needed in strengthening the elderly in facing earthquake disasters in buildings. More than 80% of the time we are in a building, whether it's our home, school, or other place. The purpose of this community service activity is to increase the capacity of the elderly to face the earthquake disaster in buildings using the singing method at the GBI Setia Bakti Kediri Elderly Posyandu. Method : The method used is to increase the capacity of the elderly to face earthquake disasters in buildings with the singing method at the GBI Setia Bakti Kediri Elderly Posyandu. Results: The results obtained in community service activities were an increase in the capacity of the elderly to face earthquake disasters in buildings using the singing method at the GBI Setia Bakti Kediri Elderly Posyandu as proven by the elderly who can answer, and practice how to save themselves when an earthquake occurs in the building by singing. . Conclusion: capacity building is important for the elderly to reduce victims in the aggregate at risk.